Narrative Review: Sistem Transportasi Publik Di Smart City Jakarta Untuk Mengurangi Kemacetan - Herdiana, Ananda Claudia (Indonesian Journal Publisher, 2025)
The Jakarta City Government has implemented various innovations in public transportation modes to attract public interest and reduce traffic congestion and air pollution. This journal discusses the application of Smart Mobility systems, which include the Commuter Line (KRL), Bus Rapid Transit (BRT), Mass Rapid Transit (MRT), and Light Rail Transit (LRT). Through the integration of transportation modes, cashless payment systems, and real-time information, Jakarta has successfully improved travel efficiency and user comfort. Data from TomTom indicates a significant decrease in traffic congestion, from 61% in 2017 to 34% in 2021. Additionally, Jakarta received the Sustainable Transport Award (STA) in 2021, signifying success in creating a sustainable transportation system. However, the implementation of Smart Mobility also faces challenges such as dependence on technology, high implementation costs, and data privacy issues. This research provides insights into the advantages and disadvantages of Smart Mobility systems and their implications for the future of public transportation in Jakarta.